ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENYULUH KB TERHADAP KUALITAS LAYANAN KADER DI KECAMATAN SUKOSEWU KABUPATEN BOJONEGORO - jurnalmap map; Sundari ÔÇÄ; Hadi Susanto; Arini Sulistyowati (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
The purpose of this study was to directly analyze the influence of motivation, competence, and training factors on the performance of family planning counselors. To analyze the influence of indirect factors of competence motivation, training on the performance of family planning counseling through the quality of cadre services. This type of research is explanatory research. This research uses a quantitative research approach. The population of this research is all family planning program cadres in Sukosewu sub-district. Bojonegoro with 116 people. Sampling technique using total sampling so that the sample in this study was 116 people. To do data analysis using path analysis. The results showed that motivation, competence and training directly had a significant effect on the performance of family planning counselors in Sukosewu District, Bojonegoro Regency. Competency motivation has an influence on the performance of family planning counseling through the quality of cadre services. Only training variables that have no influence on the quality of cadre services in Sukosewu District, Bojonegoro Regency through the performance of family planning counseling.Keywords: motivation, competence, training, performance, service quality